(untitled) (Journal of the College of Education for Women, 2019)
In this paper, visible image watermarking algorithm based on biorthogonal wavelettransform is proposed. The watermark (logo) of type binary image can be embedded in thehost gray image by using coefficients bands of the transformed host image by biorthogonaltransform domain. The logo image can be embedded in the top-left corner or spread over thewhole host image. A scaling value (α) in the frequency domain is introduced to control theperception of the watermarked image. Experimental results show that this watermarkalgorithm gives visible logo with and no losses in the recovery process of the original image,the calculated PSNR values support that. Good robustness against attempt to remove thewatermark was shown upon attempting different attacks, such as histogram equalization,double winner filtering and scaling.